Attitudes toward overtime work and self‐training: A survey on obstetricians and gynecologists in Japan. Issue 5 (10th March 2021) - Mayama, Michinori; Sekine, Masayuki; Onodera, Yohei; Suemitsu, Tokumasa; Maeda, Yuto; Nakano, Kazutoshi; Sugita, Yosuke; Ogura, Jumpei; Ohsuga, Takuma; Kodera, Chisato; Murakami, Takashi; Kido, Michiko; et al.
Abstract: Aim: The Ministry of Health, Labour, and Welfare of Japan proposed a regulation of overtime work as a reform in work style. However, the regulation may deteriorate the quality of medical services due to the reduction in training time. Thus, the study aimed to reveal perceptions in terms of generation gaps in views on self‐training and overtime work, among members of the Japan Society of Obstetrics and Gynecology (JSOG). Methods: A web‐based, self‐administered questionnaire survey was conducted among members of the JSOG. In total, 1256 respondents were included in the analysis. Data were collected on age, sex, experience as a medical doctor, location of workplace, work style, the type of main workplace, and number of full‐time doctors in the main workplace. The study examined the attitudes of the respondents toward overtime work and self‐training. The respondents were categorized based on experience as a medical doctor. Results: According to years of experience, 112 (8.9%), 226 (18.0%), 383 (30.5%), 535 (42.6%) doctors have been working for ≤5, 6–10, 11–19, and ≥ 20 years, respectively. Although 54.5% of doctors with ≤5 years of experience expected the regulation on working hours to improve the quality of medical services, those with ≥20 years of experience expressed potential deterioration. After adjusting for covariates, more years of experience were significantly related with the expectation of deterioration in the quality of medical services. Conclusions: The study revealed a generation gap in the views about self‐training and overtime work among obstetricians and gynecologists in Japan.